2021
DOI: 10.1021/acsomega.1c04398
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Behavior and Filtration of Water-Based Drilling Fluids Containing Graphene Oxide: Experimental Measurement, Mechanistic Understanding, and Modeling

Abstract: Any improvement in drilling technology is critical for developing the oil and gas industry. The success of drilling operations largely depends on drilling fluid characteristics. Drilling fluids require enough viscosity to suspend the particles and transport them to the surface and enough capability to control the fluid loss into the formation. Rheology and filtration characteristics of drilling fluids are crucial factors to consider while ensuring the effectiveness of a drilling operation. Graphene oxide (GO),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 74 publications
(99 reference statements)
0
19
0
Order By: Relevance
“…For instance, Rafieefar et al (2021) very recently reported that graphene oxide flakes (GOFs) enhanced the shear-thinning behavior by adding solely a tiny amount of GOFs to the formulation. 38 They also demonstrated the significant impact on the shear stress induced by adding 0.15 wt % GOFs to the WBDFs using 0.15 wt % XG and 0.15 wt % CMC-LV. In addition to the modulation of the shear stress, it was also reported that PV increased from 6 to 13 cP, accompanied by a fluid loss of about 18 mL/h, while the recommended value by the API is about 30 mL/h.…”
Section: Rheology and Viscoelastic Propertiesmentioning
confidence: 90%
See 4 more Smart Citations
“…For instance, Rafieefar et al (2021) very recently reported that graphene oxide flakes (GOFs) enhanced the shear-thinning behavior by adding solely a tiny amount of GOFs to the formulation. 38 They also demonstrated the significant impact on the shear stress induced by adding 0.15 wt % GOFs to the WBDFs using 0.15 wt % XG and 0.15 wt % CMC-LV. In addition to the modulation of the shear stress, it was also reported that PV increased from 6 to 13 cP, accompanied by a fluid loss of about 18 mL/h, while the recommended value by the API is about 30 mL/h.…”
Section: Rheology and Viscoelastic Propertiesmentioning
confidence: 90%
“… 84 In the study by Rafieefar et al (2021) the Herschel–Bulkley model outperformed the other two models in forecasting the rheological parameters of WBDFs using xanthan gum (XG) as a base and low-viscosity carboxymethyl cellulose (CMC-LV) with different concentrations of graphene oxide (GO) as additives. 38 , 88 Similarly, the Herschel–Bulkley parameters were calculated to evaluate the combined effect of MoS 2 nanoparticles on 80 °C thermally stable DFs. 89 Likewise, previous studies reported that the Bingham plastic model fits in a very good manner the experimental data of WBDFs using graphene nanoparticles and Laponite 2D layered nanoparticles as additives.…”
Section: Rheology and Viscoelastic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations